Social determinants of Pseudomonas aeruginosa virulence - Lee, Z-B (2022)
The understanding that bacteria possess cooperative behaviors raises new questions as to the relevance that cooperative dynamics in bacterial populations have towards issues of human health. Significant portions of the P. aeruginosa genome are dedicated to producing excreted products which, by their extracellular nature, are potentially social. Given that the benefits of these excreted products are not limited to the producing cell, the potential for social cheating arises – in which selection for nonproducing cheats becomes favored – potentially jeopardizing the overall maintenance of cooperation. The degree to which extracellular processes may be considered social, and their susceptibility to cheating, will vary depending on factors such as population structure and diffusibility.